Gambaran Hasil CT Scan pada Pasien Diabetes Melitus dengan Stroke di RSKD Dadi Makassar Tahun 2024–2025 - Muhammad Arif Taufik; Prema Hapsari Hidayati; Dian Fahmi Utami; Mochammad Erwin Rachman; Muh. Jabal Nur (Jurnal Sains dan Kesehatan, 2026)
Diabetes Mellitus (DM) is a metabolic disease with an increasing prevalence and a risk of causing macrovascular complications such as stroke. This study aimed to describe the characteristics of Diabetes Mellitus patients with stroke complications based on CT-scan results at RSKD Dadi Makassar in 2024–2025. This was a descriptive observational study with a retrospective design using medical record data. Samples were taken using a total sampling technique, comprising 60 patients, and analyzed univariately using the Statistical Product and Service Solutions (SPSS) version 26. The results showed that the majority of respondents were in the late elderly group (>56 years) at 66.7%, female (51.7%), and from the Makassar ethnic group (63.3%). Most respondents experienced hyperglycemia in random blood glucose (66.7%) and had uncontrolled fasting blood glucose (68.3%) and HbA1c (76.7%) levels. CT-scan results were dominated by non-specific cerebral infarction (68.3%), with ischemic stroke as the most common type (93.3%), a length of stay of 5–10 days (53.3%), and right-sided hemiparesis as the most common clinical manifestation (45.0%). It was concluded that DM patients with stroke complications were generally elderly, female, had poor glycemic control, and were dominated by ischemic stroke with non-specific cerebral infarction. Abstrak. Diabetes Melitus (DM) merupakan penyakit metabolik dengan prevalensi yang terus meningkat dan berisiko menimbulkan komplikasi makrovaskular berupa stroke. Penelitian ini bertujuan untuk mengetahui gambaran karakteristik pasien Diabetes Melitus yang mengalami komplikasi stroke berdasarkan hasil CT-scan di RSKD Dadi Makassar tahun 2024–2025. Penelitian ini merupakan penelitian observasional deskriptif dengan desain retrospektif menggunakan data rekam medis. Sampel diambil dengan teknik total sampling sebanyak 60 pasien dan dianalisis secara univariat menggunakan Statistical Product and Service Solutions (SPSS) versi 26. Hasil penelitian menunjukkan mayoritas responden berusia lansia akhir (>56 tahun) sebanyak 66,7%, berjenis kelamin perempuan (51,7%), dan berasal dari Suku Makassar (63,3%). Sebagian besar responden mengalami hiperglikemia pada GDS (66,7%) serta memiliki kadar GDP (68,3%) dan HbA1c (76,7%) yang tidak terkontrol. Hasil CT-scan didominasi oleh infark serebri tidak spesifik (68,3%) dengan jenis stroke terbanyak berupa stroke iskemik (93,3%), lama rawat inap terbanyak 5–10 hari (53,3%), dan manifestasi klinis tersering berupa hemiparese dextra (45,0%). Disimpulkan bahwa pasien DM dengan komplikasi stroke umumnya berusia lanjut, berjenis kelamin perempuan, memiliki kontrol glikemik yang buruk, dan didominasi oleh stroke iskemik dengan gambaran infark serebri tidak spesifik.